Use of 3D anatomical models in mock circulatory loops for cardiac medical device testing. Issue 2 (12th November 2022) - Rocchi, Maria; Ingram, Marcus; Claus, Piet; D'hooge, Jan; Meyns, Bart; Fresiello, Libera
Abstract: Introduction: Mock circulatory loops (MCLs) are mechanical representations of the cardiovascular system largely used to test the hemodynamic performance of cardiovascular medical devices (MD). Thanks to 3 dimensional (3D) printing technologies, MCLs can nowadays also incorporate anatomical models so to offer enhanced testing capabilities. The aim of this review is to provide an overview on MCLs and to discuss the recent developments of 3D anatomical models for cardiovascular MD testing. Methods: The review first analyses the different techniques to develop 3D anatomical models, in both rigid and compliant materials. In the second section, the state of the art of MCLs with 3D models is discussed, along with the testing of different MDs: implantable blood pumps, heart valves, and imaging techniques. For each class of MD, the MCL is analyzed in terms of: the cardiovascular model embedded, the 3D model implemented (the anatomy represented, the material used, and the activation method), and the testing applications. Discussions and Conclusions: MCLs serve the purpose of testing cardiovascular MDs in different (patho‐)physiological scenarios. The addition of 3D anatomical models enables more realistic connections of the MD with the implantation site and enhances the testing capabilities of the MCL. Current attempts focus on the development of personalized MCLs to test MDs in patient‐specific hemodynamic and anatomical scenarios. The main limitation of MCLs is the impossibility to assess the impact of a MD in the long‐term and at a biological level, for which animal experiments are still needed. Abstract : This review analyses the state of the art of mock circulatory loops implementing 3D anatomical models for the testing of different medical devices such as implantable blood pumps, heart valves, and imaging techniques. Each mock circulatory loops is analysed in terms of the cardiovascular model embedded, and of the 3D model implemented (the anatomy represented, the material used, and the activation method).